A arte e a cultura em tempos de pandemia: os vários vírus que nos assolam - Calabre, Lia (Universidade de São Paulo | Escola de Comunicações e Artes, 2020)
This article presents some reflections about art and culture environment, as well as the public policies developed for this sector, before the Covid-19 pandemic in Brazil. The research also presents the urgency that this new situation represents to the culture sector, and the article also discuss the federal Bill No. 1,075 of 2020, which is responsible for emergency actions to the culture sector.